Effects of exercise information using social network service(SNS) on physical activity and psychological variables among inactive college students - Dojin An; Youngho Kim; Soojin Kang (Korea Institute of Sport Science, 2020)
Purpose The current study investigated the effects of exercise information using social network service(SNS) to identify changes of physical activity and psychological variables among inactive college students. Methods Inactive college students(30 experimental group, 30 control group) were voluntarily participated in the 12-weeks intervention. During this period, the experimental group received exercise information through SNS. And all study participants' physical activity, stages of physical activity, self-efficacy, motivation, and perceived benefits and barriers were measured at the pre, mid and post intervention. Frequency analysis, chi-square test, 2-way ANOVA RM were conducted to analyze data obtained in the study. All procedures were performed by using SPSS 23.0. Results The exercise information intervention using SNS during 12 weeks had a positive effect on the stages of physical activity of inactive college students, and there were statistically significant differences. In addition, physical activity, perceived benefits and barriers, self-efficacy, motivation positively improved after the intervention, but there were no statistically significant differences between experimental and control group. Conclusions The present study suggests that psychological strategies using various SNS programs have positive effects for inactive college students to increase physical activity and its related psychological variables.